Formation of a protein corona around nanoparticles. (June 2019) - Zhdanov, Vladimir P.
Abstract: In biofluids, nanoparticles rapidly become surrounded by a protein corona. This phenomenon started to attract attention 10 years ago. Since then, this subfield of colloid and interface science was among the most rapidly expanding and progressing. Owing to its strong relation to biology and applications, this area is rich in various questions to explore. The reviews of the corresponding experiments are already numerous. Herein, I focus on the related theory including conventional mean-field kinetic models, dynamic density functional theory, Monte Carlo simulations, and molecular dynamics simulations. The key concept here is that the formation of a protein corona depends on the interplay of competition of different proteins for the location near the nanoparticle–solution interface (Vroman effect) and denaturation at this interface. Although this concept is not new, many details of this interplay are still open for debate.